CULTURAL BIAS IN LANGUAGE TESTING - Patrisius Istiarto Djiwandono (TEFLIN, 2006)
Abstract: An issue that has recently been gaining more attention in the domain of language testing is item bias. Defined as the characteristic of an item which causes learners of the same abilities but of different social groups to perform differently, the bias can be present as gender, ethnic, religious, social class, or cultural bias. The paper brings up a discussion in this area of concern by starting off from the concept of culture. It then explains what cultural bias is, how it manifests in items of language tests, and what unfavorable results may happen. It then highlights some examples of cultural bias in some popular standardized tests constructed by both foreign institutions and domestic educational bodies. The paper argues that if language teaching is to foster the development of cross-cultural understanding, attempts should be made to eliminate such bias. It then concludes by discussing Differential Item Functioning, a method that is used for dealing with bias in language tests.